Mitral Valve Repair in Nursing Care - Jabour, Hashima Makki Mohammed; Mariam Mohammed arar Rahem; Maryam Jubran Jaber Mahnshi; Noura Qasim Ghalfan Khurmi; Khawlah Fahad Almutawa; Rashed Barrak Albarrak; Mona Ali Alsomali; Doaa Salim Hamid Alabsi; Weam Ali Esmael Mobarky; Samira Ali Alsumali; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Mitral valve disease, particularly mitral regurgitation and mitral stenosis, represents a significant cause of cardiovascular morbidity and mortality worldwide. Mitral valve repair is widely recognized as the preferred therapeutic option for degenerative mitral valve disease due to its superior clinical outcomes compared with valve replacement. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This paper aims to review mitral valve repair with a focus on its anatomical considerations, clinical indications, surgical techniques, complications, and the essential role of nursing care in optimizing patient outcomes. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive narrative review was conducted using current clinical guidelines and evidence-based literature addressing mitral valve anatomy, pathology, indications for repair, operative techniques, postoperative complications, and interprofessional nursing management. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Mitral valve repair demonstrates reduced operative mortality, improved preservation of left ventricular function, and enhanced long-term survival, especially in primary degenerative mitral regurgitation. Early surgical intervention, accurate patient selection, and experienced surgical teams are key factors influencing success. Nursing and allied health interventions significantly contribute to postoperative recovery, complication prevention, and patient education. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Mitral valve repair remains the gold standard for suitable patients with mitral valve disease. Integrating surgical expertise with comprehensive nursing care improves clinical outcomes, promotes recovery, and enhances quality of life.